E-J Summability of Orthogonal Series - Akgun, F. Aydin; Rhoades, B. E. (NEW YORK BUSINESS GLOBAL LLC, 2020)
In this paper we obtain a sufficient condition for the E-J summability of certain orthogonal series. Our results generalize the corresponding theorems for ordinary Hausdorff summability obtained by Kalaivana and Youvaraj.
Keywords: E-J matrices; orthogonal series; SUMMATION METHODS; MOMENT SERIES; Mathematics